Routing with a clue. - Bremler-Barr, Anat (Computer communication review.)
We suggest a new simple forwarding technique to speed-up IP destination address lookup. The technique is a natural extension of IP, requires 5 bits in the IP header (IPv4, 7 in IPv6) and performs IP lookup nearly as fast as IP/Tag-switching but with a smaller memory requirement and a much simpler protocol. The basic idea is that each router adds a "clue" to each packet, telling its downstream router where it ended the IP lookup. Since the forwarding tables of neighboring routers are similar, the clue either directly determines the best prefix match for the downstream router, or provides the downstream router with a good point to start its IP lookup. The new scheme thus prevents repeated computations and distributes the lookup process across the routers along the packet path. Each router starts the lookup computation at the point its up-stream neighbor has finished. Furthermore, the new scheme is easily assimilated into heterogeneous IP networks, does not require routers coordination, and requires no setup time. Even a flow of one packet enjoys the benefits of the scheme without any additional overhead. The speedup we achieve is about 10 times faster than current standard techniques. In a sense this paper shows that the current routers employed in the Internet are clue-less; Namely, it is possible to speedup the IP-lookup by an order of magnitude without any major changes to the existing protocols.